A social safety net? Rejection sensitivity and political opinion sharing among young people in social media. (February 2019) - Bäck, Emma A; Bäck, Hanna; Fredén, Annika; Gustafsson, Nils
One reason why people avoid using social media to express their opinions is to avert social sanctions as proposed by the spiral of silence theory. We here elaborate on individual-level sensitivity to social rejection in relation to voicing political opinions on social media sites. Given the uncertainty about sharing political views in social media, and the fact that social acceptance, or rejection, can be easily communicated through, for instance, likes, or a lack of likes, we argue that rejection sensitive individuals are less likely to share political information in social media. Combining an analysis of unique survey data on psychological characteristics and online political activity with focus group interviews with Swedish youth supports our argument, showing that rejection sensitive individuals are less inclined to engage politically in social media. The results extend on previous research by establishing the role of rejection sensitivity in political engagement in social media.